Picture-Based Insurance (PBI) - Ceballos, Francisco; Kramer, Berber; Robles, Miguel (2018)
A formative evaluation on using smartphone camera data for crop insurance in northwest India. Presented by IFPRI Senior Research Analyst Francisco Ceballos, With Berber Kramer (IFPRI Research Fellow ) and Miguel Robles ( ‎Advisor to Executive Director for Argentina, Bolivia, Chile, Paraguay, Peru and Uruguay, World Bank)